THEORETICAL STUDY OF SHOCK WAVES ON CYLINDRICAL PANELS LOCATED IN LIQUID MEDIUM. (UBS Scientific Bulletin, 2024)
This scientific article examines the issues that arise during the interaction of a plane pressure shock wave with an elastic round cylindrical panel. In an ideal liquid there is a cylindrical panel attached to a cylindrical screen. According to the theory of thin shallow shells, the transverse vibrations of the panel are described by the well-known equations of finite deflections. The problem of nonlinear motion of an elastic panel under the action of a weak shock wave is a complex problem. To simplify the problem, the pressure of reflected and radiated waves is determined approximately without taking into account diffraction at the edges of the boundary. Based on these simplifications, the basic formulas for a smooth cylindrical shell are derived. Using the Maple-17 program, nonlinear differential equations of motion of a cylindrical panel placed in an ideal fluid are numerically solved. The results obtained show that the vibrations of the panel in an ideal fluid are close to aperiodic. This is due to its high damping.